Maria Madalena : lágrimas, amor e culpa - Fardilha, Luís de Sá (1995)
The author identifies and studies the references to St Mary Magdalene in Portuguese poetry of the 16th-18th centuries, dealing with the forms and meanings taken by the figure of the "beata peccatrix" in the cultural and spiritual context of the period. As a metaphor of penitence and as a symbol of mystic love, the Saint appears at the core of religious controversies raised by the protestant and catholic reformations. The personal and privileged relationship of the Saint to Christ, however, is the main feature that defines her permanence and salience in the work of Portuguese poets over that periodof three centuries.